Prevalence and epidemiology of gastro-intestinal parasitic infections in the mitidja plain (Algeria) - Samira, Zamiche (STUDIES IN HEALTH SCIENCES, 2024)
Gastrointestinal parasitosis is a major public health issue worldwide, affecting millions of people, particularly in areas where socio-economic and environmental conditions are precarious. In Algeria, the agricultural region of the Mitidja Plain is particularly vulnerable to gastrointestinal pathologies due to favorable climatic and socio-economic factors. This study aims to analyze the epidemiology of gastrointestinal parasitoses within the Mitidja population through a retrospective analysis of medical records from patients presenting digestive disorders at various hospitals in the region between January 2018 and December 2023. The analysis revealed a significant prevalence of intestinal parasitoses, with nearly half of the subjects infested by at least one parasite, pathogenic or not. Thirteen parasitic species were identified, including 10 protozoa and 3 helminths, with protozoa predominating at 77 % of cases. The most frequently encountered species were Blastocystis hominis (27.5 %), Endolimax nana (21%), and Entamoeba histolytica (13%). The helminths identified included Enterobius vermicularis and, Taenia solium, with a prevalence of 1.55% and 1% respectively. The preliminary results underscore the need for further analysis by enhancing sampling processes and extending the study period. Additionally, implementing preventive measures such as educating the population about fecal hygiene, ensuring proper sanitation facilities, and treating water and food intended for consumption is crucial for effectively combating these fecal-transmitted parasites.